Plan de negocios de una finca productora de café para la implementación de una marca propia de café orgánico en Santander, Colombia (2018)
The following document is made with the intention of creating an own coffee brand company in the different municipalities of the department of Santander, in Colombia. For this purpose, a prospective market analysis was carried out with a survey in the population to determine the purchase intention of the product, in one hand this survey had the final intention to evaluate if Santander department inhabitants are capable to acquire the product for their homes consumption, on the other hand, an external evaluation was made to define the main competitors of this area in the country and the department to determine the most bought and consumed coffee brands by the inhabitants.